2016
DOI: 10.1055/s-0042-108807
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stretching does not Change the Stiffness of the Muscle-Tendon Unit

Abstract: The purpose of this study was to identify changes in ankle range of motion and passive mechanical properties of the muscle-tendon unit after dynamic stretching. 12 healthy subjects participated in this study. Displacement of the muscle-tendon junction was measured using ultrasonography while the ankle was passively dorsiflexed at 1°/sec to its maximal dorsiflexion angle. Passive torque was also measured using an isokinetic dynamometer. Measurements were conducted pre-intervention, immediately after the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 36 publications
2
32
2
1
Order By: Relevance
“…Recently, Pamboris et al 38 found a decrease in muscle fascicle strain combined with an increase in muscle stiffness (measured by shear wave elastography) attributing the increase to ankle dorsiflexion RoM to increased tendon strain. Mizuno and Umemura 16 reported an increase in maximum passive ankle dorsiflexion RoM without changing the passive stiffness of the MTU attributing it to an increase in pain tolerance. Our results cannot refute that alteration in pain tolerance (ie, discomfort or pain perception at a given ROM) is a contributing mechanism to the increased RoM changes after stretching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Pamboris et al 38 found a decrease in muscle fascicle strain combined with an increase in muscle stiffness (measured by shear wave elastography) attributing the increase to ankle dorsiflexion RoM to increased tendon strain. Mizuno and Umemura 16 reported an increase in maximum passive ankle dorsiflexion RoM without changing the passive stiffness of the MTU attributing it to an increase in pain tolerance. Our results cannot refute that alteration in pain tolerance (ie, discomfort or pain perception at a given ROM) is a contributing mechanism to the increased RoM changes after stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Direct stimulation is considered necessary to change the mechanical behavior of the MTU . Thus, studies in which DS involved “agonist” muscle group contractions demonstrated decreased in mechanical behavior, while in Mizuno and Umemura, whose DS protocol involved “antagonist” muscle group contractions, there was no change in MTU behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible factors involved in DS include dynamic stretching and shortening of actively contracting muscles, which might be responsible for the smaller negative effect of DS on muscle functions. This can be due to a retained neural drive and/or a negligible change in MTU stiffness after DS [10,11].…”
Section: Introductionmentioning
confidence: 99%